Basal and Calcium-Stimulated Procalcitonin for the Diagnosis of Medullary Thyroid Cancers: Lights and Shadows - Censi, Simona; Di Stefano, Marta; Repaci, Andrea; Benvenuti, Teresa; Manso, Jacopo; Pagotto, Uberto; Iacobone, Maurizio; Barollo, Susi; Bertazza, Loris; Galuppini, Francesca; Benna, Clara; Pennelli, Gianmaria; et al. (Frontiers in Endocrinology, 2021)
Background: procalcitonin (proCt) was recently proposed as an alternative or in addition to calcitonin (Ct) in medullary thyroid cancer (MTC) diagnostics. Methods: serum basal Ct (bCt) and proCt (bproCt) levels were measured before surgery from a consecutive series of patients with (n=43) and without (n=75) MTC, retrospectively collected in Padua. Serum bproCt, bCt and stimulated proCt and Ct (sproCt and sCt) were measured in another consecutive series of 33 patients seen at three tertiary-level institutions underwent a calcium stimulation test prior to surgery, 20 of them with a final diagnosis of MTC, and 13 with non-MTC nodular disease. Results: median bproCt levels were higher in MTC than in non-MTC. A positive correlation was found for bproCt with bCt (P<0.01, R2=0.75), and with tumor size (P<0.01, R2=0.39). The cut-off for bproCt differentiating between MTC and non-MTC patients was >0.07 ng/ml (sensitivity: 85.7%, specificity: 98.9%, positive predictive value [PPV]: 98.2%, negative predictive value [NPV]: 90.6%, P<0.01). While bproCt was >0.07 ng/ml in 38/39 (97.4%) patients with MTC >10 mm, it was only above said cut-off in 15/23 (65.2%) patients with tumors ≤10 mm. A sproCt >0.19 ng/ml was able to identify MTC (sensitivity: 90.0%, specificity:100.0%, PPV: 100.0%, NPV: 86.7% [P<0.01]). Conclusions: proCt cannot replace Ct as the standard of care in the MTC diagnosis, because it often fails to identify a small MTC. That said, it has a very high specificity and can be used in combination with Ct in MTC diagnostics, particularly in the case of mildly elevated basal Ct levels.